2020
DOI: 10.1088/1361-6463/ab813f
|View full text |Cite
|
Sign up to set email alerts
|

VUV radiation flux from argon DC magnetron plasma

Abstract: Vacuum ultraviolet (VUV) flux of argon plasma radiation in a DC magnetron discharge with a plane circular titanium cathode is measured. It is found that the intensity of VUV radiation, mainly indicated by the resonance lines of argon atoms at 104.8 and 106.7 nm and ions at 92 and 93.2 nm, is proportional to the discharge current and decreases with pressure. Following the results of the measurements, a numerical model of resonance radiation transport is developed to determine the VUV flux to the substrate place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…[24] All these lines have an energy higher than the bandgap of SiO 2 and OSG materials. The VUV flux of an argon direct current (DC) magnetron discharge plasma was measured by Pal et al, [25] and the flux was proportional to the discharge current and decreased with pressure. In the experiments of Boffard et al [26,27] it is shown that the VUV radiation flux in Ar ICP discharge depends nonmonotonically on the gas pressure, reaching maximum values at pressures near 10 mTorr in the case of argon.…”
Section: Introductionmentioning
confidence: 99%
“…[24] All these lines have an energy higher than the bandgap of SiO 2 and OSG materials. The VUV flux of an argon direct current (DC) magnetron discharge plasma was measured by Pal et al, [25] and the flux was proportional to the discharge current and decreased with pressure. In the experiments of Boffard et al [26,27] it is shown that the VUV radiation flux in Ar ICP discharge depends nonmonotonically on the gas pressure, reaching maximum values at pressures near 10 mTorr in the case of argon.…”
Section: Introductionmentioning
confidence: 99%
“…A typical problem in magnetron discharge is also the presence of sputtered atoms of cathode material that can contaminate the detector (VUV photodiode) surface. Pal et al [ 33 ] used a fluorescence detector of sodium salicylate to measure the VUV fluxes from argon plasma of DC magnetron discharge far from the substrate, and they estimated the VUV flux on the substrate located near the sputtering cathode using a numerical model of resonance radiation transport. The discharge current varied from 0.3 to 2 A, and discharge voltage from 324 to 437 V for the pressure of 2 mTorr, and from 281 to 364 V for 12 mTorr.…”
Section: State Of the Art And Correlationsmentioning
confidence: 99%
“…Pal et al [33] X Iglesias et al [34] X Es-sebbar et al [35] X X Iglesias et al [36] X X Proshina et al [37] X Fantz et al [38] X X X Tigrine et al [39] X X Zotovich et al [40] X X Es-sebbar et al [41] Relative intensities X Rakhimova et al [42] X Boffard et al [43] X X X Zaima et al [44] Lee et al [45] Relative intensities X X Pargon et al [46] X Jinnai et al [47] X X Titus et al [48] X X X X Woodworth et al [49] X Barton et al [50] X X Abbreviation: VUV, vacuum ultraviolet.…”
Section: Vuv Effect On Materialsmentioning
confidence: 99%
See 2 more Smart Citations